PARENTAL CHARACTERISTICS AND INFANT PSYCHOSOCIAL DEVELOPMENT - PH to Lebanon (Medical Studies and Health Journal (SEHAT), 2024)
The infant period (0-18 months) is a very important part of growth because it is a phasegolden age. During this period, there are infants who experience psychosocial delays due to direct involvement or parental stimulation. This research was conducted to determine the characteristics of parents (age, gender, education, occupation, income and family type) and the psychosocial development of infants. The research used an exploratory descriptive design. The sample in the study consisted of 55 respondents with data collection techniques using total sampling. The measuring tools are in the form of questionnaires, namely the parent characteristics questionnaire and the infant psychosocial development questionnaire (0-18 months). Data analysis uses frequency distribution. Research shows that the majority of parents are >25-40 years old, female, have junior high school education, work as laborers, average income <UMR, and all respondents belong to nuclear families. Meanwhile, the majority of infants' psychosocial development is at a normal stage. Parents are expected to carry out self-evaluations in getting to know, caring for and providing stimulation to infant children in order to achieve optimal psychosocial development.